Defining skill sets requirements for Agile Scrum team formation - Omar, Mazni; Ahmad Khasasi, Noor Liza; Syed Abdullah, Sharifah Lailee; Hashim, Nor Laily; Romli, Rohaida; Katuk, Norliza (Medwell Publishing, 2018)
Agile Scrum Software development methodology has been accepted widely by the Software Engineering (SE) community.This is mainly due to agile principles that emphasize on rapid development process which enables working quality software to be delivered on time. Successful Agile Scrum project depends on the high-performance of team members that assigned to a specific software project.Therefore, Scrum project highly demand the right person to be assigned as a team member.Due to this, skill sets requirements among team members are significant for the project manager to select the best team.There are two types of skills for team members that need to be identified-hard skills and soft skills.Thus, this study aims to define each of the skills set requirements based on review of literature and expert's opinions.It is hoped that the defined skills set requirements can serve as a guideline to develop a comprehensive Agile team formation method.